2020
DOI: 10.1017/exp.2020.22
|View full text |Cite
|
Sign up to set email alerts
|

Salinity decreases transpiration of sorghum plants

Abstract: Growing in a saline environment causes changes in important physiological processes that are directly related to plant growth and development. In this study we evaluated the effect of salinity on transpiration of sorghum plants in semi-arid conditions and found that the highest rates of transpiration were observed in the hottest hours of the day, between 10 a.m. and 3 p.m., with plants subjected to the saline environment having their transpiration reduced by up to 70% when compared to the non-saline environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…Sorghum (Sorghum bicolor (L.) Moench) is a tolerant/resistant crop to several abiotic constraints (Gois et al, 2019;Safdar et al, 2019;Shankar & Evelin, 2019;Castro & Santos, 2020). Its agricultural exploitation in semiarid regions is subject to several adverse environmental factors, potentially capable of causing negative effects on growth, development, production, and quality Simões et al, 2019;Guimarães et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum (Sorghum bicolor (L.) Moench) is a tolerant/resistant crop to several abiotic constraints (Gois et al, 2019;Safdar et al, 2019;Shankar & Evelin, 2019;Castro & Santos, 2020). Its agricultural exploitation in semiarid regions is subject to several adverse environmental factors, potentially capable of causing negative effects on growth, development, production, and quality Simões et al, 2019;Guimarães et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As observed in the current study, decreased stomatal and chlorophyll concentrations may lead to lower radiation usage efficiency and carbohydrate synthesis, resulting in lower plant growth and biomass in salt‐stressed plants. Guimarães et al ( 2020 ) reported that the transpiration of salt‐sensitive sorghum plants decreased by up to 70% under salt stress compared with that in control plants. Ibrahim et al ( 2020 ) found that the stomatal conductance of sorghum decreases considerably with increasing soil salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Las plantas son un sistema dinámico y flexible capaz de adaptarse a cualquier cambio en su entorno (Arsova et al, 2019). El estrés por salinidad induce cambios morfológicos, fisiológicos y bioquímicos en las plantas, y puede provocar estrés iónico, estrés osmótico y estrés oxidativo, en las plantas (Machado-Guimarães et al, 2020). A su vez, el estres iónico es causado por la acumulación de iones de sal en las células de la planta por lo que se genera una deficiencia de nutrientes (Hernández, 2019;Wani et al, 2020).…”
Section: Discussionunclassified
“…La salinidad induce un amplio espectro de alteraciones fisiológicas (conductancia estomatica, tasa de transpiración y fotosíntesis), biometrícas (altura, área foliar, producción de biomasa) y bioquímicas (enzimas antioxidantes), y puede provocar estrés iónico, estrés osmótico y estrés oxidativo en las plantas (Machado-Guimarães et al, 2020). El estres iónico es causado por una mayor acumulación de iones de sal en las células de la planta a niveles tóxicos, y el estrés osmótico es causado por una disminución en el potencial osmótico del agua, además el estres ionico provoca una deficiencia de nutrientes, perturba el equilibrio de las especies reactivas de oxígeno (ROS) en las células de las plantas, lo que causa directamente el estrés oxidativo (Hernández, 2019;Wani et al, 2020).…”
unclassified